Do We Need a Celebrity Endorser? Study based on Source Credibility Model in Intention to Make Investment - Widyasari, Suzy; Santoso, Ignatius Hari; Maskur, Ali (Review of Management and Entrepreneurship, 2024)
We often hear about various cases of fraud or inappropriate investment practices in Indonesia, one of which was carried out by DNA Pro. This study aims to investigate the impact of celebrity endorsers on investment decisions, particularly in the DNA Pro trading robot case, where the total public loss due to the alleged illegal investment is estimated at 97 billion rupiah. Unfortunately, many artists are endorsers and influencers from these various online investment platforms. The number of celebrity endorsers has succeeded in attracting the interest of many potential investors. The method used in this study was a quantitative approach, utilizing the Smart PLS application version 4. Thus, the effectiveness of celebrity endorsers as an attraction is still something to consider. This study aims to reaffirm whether each construct in the Source Credibility Model still significantly influences the formation of product purchase intentions or is only limited to the popularity of the endorser. The findings of this research proved that the intention to purchase investment products can only be formed by the celebrity attractiveness construct alone.